THE IMPACT OF EARLY EDUCATION ON A CHILD’S LIFE AND THE SIGNIFICANCE OF EDUCATION DEVELOPMENT - Turobjonova MohiNur Tohirjon daughter (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article is focused on the impact of early education on a child’s life and the significance of education development, which is important for students, parents, and teachers. This topic is essential for parents and teachers to prepare students well and provide them with support. This article discusses the impact of early education on a child’s life, ways in which children can understand and learn, the importance of self-development and motivation in education, and methods for parents and teachers to prepare and support their students. This article provides general information on the significance of early education and education development, and helps students, parents, and teachers understand the importance of education.